Trifolin inhibits the calcium-driven contraction pathway in vascular smooth muscle - Li, Renfeng; Wu, Jinkong; Wu, Meizhu; Ali, Farman; Yang, Yanyan; Chen, Hong; Guo, Zhi; Lian, Dawei; Shen, Aling; Peng, Jun (Frontiers in Pharmacology, 2025)
Trifolin, a bioactive component of the Qingda granule, has demonstrated significant antihypertensive potential; however, its precise mechanisms of action remain largely unknown. This study aimed to investigate the antihypertensive effects of trifolin and unravel its underlying molecular mechanisms. The influence of trifolin on vascular contraction and relaxation and its regulatory effects on ion channels were evaluated through a vascular tension experiment. Morphological changes in the aortic tissues of mice with angiotensin Ⅱ-induced hypertension and the expression profiles of contraction-associated proteins were analyzed via hematoxylin-eosin staining and immunohistochemistry. Additionally, trifolin’s impact on calcium ion dynamics and contraction-associated protein expression in angiotensin Ⅱ-activated vascular smooth muscle cells (VSMCs) was determined through calcium flux assays and western blot analyses. Trifolin treatment decreased the constriction of isolated abdominal aortic rings induced by norepinephrine, KCl, and angiotensin Ⅱ in an endothelium-independent manner and extracellular Ca2+ influx induced by these three substances and thapsigargin. Moreover, trifolin treatment significantly reduced the abdominal aortic wall thickness and downregulated the expression of store-operated channels channel proteins (STIM1 and ORAI1) and calcium signaling-related proteins (CaM, myosin light chain kinase, and p-MLC2) in the abdominal aorta of hypertensive mice and angiotensin Ⅱ-induced VSMCs. In conclusion, calcium signaling inhibition may underlie trifolin’s antihypertensive effects and its ability to ameliorate vascular function. These findings offer new therapeutic insights for hypertension treatment.